“And Some Guys Dream Bad Things” - Robert Brightman (Semiotic Review, 2015)
Crees conceive themselves simultaneously as hunters of animals and as the prey of monsters who are the hunters of humans. For Rock Crees and other boreal forest Algonquians, the noun wihtikow, and its cognates refer either to an anthropophagous monster or to a human individual exhibiting symptoms of transformation into such a monster. Rock Crees say that all witikos were formerly human beings. Humans are said to have become witikos through dream predestination, possession, freezing, and commission of famine cannibalism. Fogelson (1980:147–48) once remarked on the cross-cultural generality of oppositive relations between monstrous and human categories: "On a more general level, it should be pointed out that monsters cannot exist except in classificatory relation to others. Thus a universal function of monsters is to define what is human through contrast and opposition." From this point of view, humanity monstrously distorted throws into relief the defining characteristics of the human condition. As I show, Witiko traits comprise a systematic oppositional inversion of traits Crees understand as constitutive of the human state, or, more specifically, of the state of nihiðawiwin 'Cree-ness'. It is as if the image of the witiko has been constructed on the basis of successively more inclusive reflections on defining human attributes. (This article is a reprint of “And Some Guys Dream Bad Things,” the fifth chapter of Grateful Prey: Rock Cree Human-Animal Relationships, by Robert Brightman, © 1993 by the Regents of the University of California; published by the University of California Press, reproduced with permission. Full version here: ark.cdlib.org/ark:/13030/ft0f59n6tb/. Please also see "The Return of the Windigo, Again: Part II" in this issue.)